2007
DOI: 10.1002/tox.20229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary boron on cervical cytopathology and on micronucleus frequency in exfoliated buccal cells

Abstract: Recent evidence indicates that boron and borates may have anticarcinogenic properties. In this study, we have investigated the incidence of adverse cytological findings in cervical smears and the micronucleus (MN) frequency in women living in boron-rich and boron-poor regions. Cervical smears were prepared from 1059 women with low socioeconomic status; 472 of the women lived in relatively boronrich rural areas, while 587 lived in relatively boron-poor regions. The average and standard deviation values for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 47 publications
2
45
0
6
Order By: Relevance
“…Previous studies have shown that the fountain and tap water in this area contain 2 mg/l or higher levels of B 15,21 . The levels of B exposure of these subjects were compared with those of controls selected among the residents of Balıkesir and Ankara city centres.…”
Section: Geographic Locations and Samplingmentioning
confidence: 79%
See 2 more Smart Citations
“…Previous studies have shown that the fountain and tap water in this area contain 2 mg/l or higher levels of B 15,21 . The levels of B exposure of these subjects were compared with those of controls selected among the residents of Balıkesir and Ankara city centres.…”
Section: Geographic Locations and Samplingmentioning
confidence: 79%
“…The main sources of B are drinking water and consumption of locally grown agricultural products 15,21 . In fact, determination of B in agricultural products from this area gave relatively high concentrations 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that boron compounds (such as borax, boric acid) are non-genotoxic agents on human blood cells (Turkez et al , 2010Geyikoglu and Turkez 2008;Turkez 2008). Furthermore, boron compounds have attracted much interest with respect to their protective effect against free radical damage that may be the cause of many diseases including cancer (Korkmaz et al 2007;Mahabir et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Çeşitli epidemiyolojik ve hücresel çalışmalarda borun bazı kanser türlerine karşı koruyucu özellikte olabileceği ileri sürülmüş özellikle prostat kanseri hücrelerinde bor uygulanmasıyla doz ve maruziyet süresine bağlı olarak bu hücre hatlarının proliferasyonunda düşüşler tespit edilmiştir [9,10]. Bor yönünden zengin bölgede yaşayan insanların bu kanser türleri açısından bor yönünden fakir bölgede yaşayan insanlardan daha az kanser insidansı taşıdığı saptanmıştır [7,11,12]. Korkmaz (2007) …”
unclassified